Characterization of inhibitory supernatants produced by bacteria isolated from goat milk (Research, Society and Development, 2022)
Several compounds can be produced by lactic acid bacteria (LAB) isolated from milk such as bacteriocins, small cationic and thermostable peptides, that possess antimicrobial activity. The technological application of these antimicrobial compounds became important for the industry mainly because of chemical preservatives. This study aimed to isolate LAB with anti-Listeria monocytogenes activity from raw goat milk and to characterize their inhibitory cell-free supernatants (CFS). It was performed Isolation of LAB from raw goat milk, inhibitory activity of the CFS, characterization of CFS inhibitory activity under different conditions, mode of action of the active CFS, adsorption of the anti-Listeria substances present in the CFS of LS2 to L. monocytogenes, molecular identification of LAB isolates with anti-Listeria activity. Three isolated strains produced CFS with active inhibitory substances of proteinaceous nature, identified by 16S rDNA as Weissella cibaria (LS1) and Lactococcus lactis (LS2 and LS3). The CFS of LS2 showed the highest anti-Listeria activity (1600 arbitrary units/mL) after 2 h at pH 6.0 and was bacteriostatic and active at low pH at temperatures of 4 °C to 80 °C. The results suggest that the LS2 strain is a biopreservative culture with potential for applications to control L. monocytogenes in foods.